Determinant of Intention to Purchase Halal Cosmetics: A Millennial and Z Generation Perspective - Nurcahyono, Nurcahyono; Hanifah, Asma' (UNISSULA, 2023)
In recent years, the halal industry has become a trend, this is because the Indonesian people have begun to apply halal culture as a lifestyle. This article aims to determine the factors influencing the purchase intention of halal cosmetics among millennials and generation Z. The author uses the theory of planned behavior to identify factors that encourage a person's intention to buy halal cosmetics among millennials and generation Z. The variables or predictors are attitudes, halal awareness, subjective norms, knowledge, halal labels, buying behavior, brand image, psychological risk, social media, and religiosity. This study has advantages compared to others because it uses a psychological approach in the form of buying and risk behavior and uses the effects of social media. The data was obtained through a survey conducted by the millennial generation and generation Z, who live in the city of Semarang. The sampling method used was non-probability with a purposive sampling technique. The data analysis of this research used Structural Equation Modeling (SEM) – Partial Least Square (PLS) with WarpPLS application. Testing is done using the measurement, goodness of fit, and structural models. The results showed that the factors influencing the purchase of halal cosmetics are attitudes, subjective norms, knowledge, halal labels, buying behavior, brand image, psychological risk, and religiosity. However, the halal awareness variable, social media, is not a determinant of someone buying halal cosmetics. The results show that the halal awareness of research respondents is still low because they have not fully paid attention to the halal aspect. Currently, social media provides too much information, making it difficult to distinguish whether it is credible or not, so respondents choose other alternatives.